2017
DOI: 10.1017/s1751731117000970
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pre-slaughter mortality in turkeys and end of lay hens

Abstract: Pre-slaughter transportation may affect poultry welfare and mortality rates. A retrospective analysis was conducted to examine the effect of environmental, management and individual factors on the percentage of dead birds during pre-slaughter transportation (dead-on-arrival, DOA). The variables accounted for in the analyses included: environmental temperature, travel duration, genetic line, gender, crate type and crate stocking density. Among the 41 452 loads of turkeys (34 696 388 birds) and 3241 of end of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This could be caused by challenging climate conditions in Turkey and may be due to longer transport distances. Previous studies also found a higher mortality rate in cold seasons [ 5 , 12 , 16 , 25 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This could be caused by challenging climate conditions in Turkey and may be due to longer transport distances. Previous studies also found a higher mortality rate in cold seasons [ 5 , 12 , 16 , 25 ].…”
Section: Discussionmentioning
confidence: 64%
“…The negative effect of longer transport distances on poultry welfare was also shown in previous studies. Many previous studies on end-of-lay hens found that longer transportation distances increase the mortality rate of animals [ 5 , 9 , 12 , 16 ]. The DOA rate in the current study was higher than in previous studies because the hens in this study were transported longer distances and might have faced harder climate conditions than those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, footpad lesions are reported to be strongly related to litter moisture and season, rather than SD per se [ 19 ]. Finally, the threshold for DOA does not reflect average values (around 0.33%) [ 20 ] and is influenced by transport condition, rather than by the husbandry system itself [ 21 ]. No threshold for AMU is currently set by health authorities in relationship with SD, and it cannot be excluded that a higher AMU is needed to keep mortality and footpad lesions under control, as they are partly determined by enteric dysbiosis that worsen litter quality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences are difficult to interpret due to dissimilarities in used methodologies. Knowing that turkeys have a higher predisposition for disease and a longer production cycle, leading to build-up of litter or more environmental stressors, a higher AMU in turkeys compared to broilers is expected [16,[37][38][39].…”
Section: Amu At Turkey Farmsmentioning
confidence: 99%